2021
DOI: 10.1080/21642850.2021.2014851
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pregnancy as a teachable moment for behaviour change: a comparison of the COM-B and teachable moments models

Abstract: Objectives Theoretical models have informed the understanding of pregnancy as a ‘teachable moment’ for health behaviour change. However, these models have not been developed specifically for, nor widely tested, in this population. Currently, no pregnancy-specific model of behaviour change exists, which is important given it is a unique yet common health event. This study aimed to assess the extent to which factors influencing antenatal behaviour change are accounted for by the COM-B model and Teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These include the physical environment and aspects of the social environment, and the influence of pregnancy symptoms. This is consistent with what has previously been reported in the literature [ 31 ]. However, the findings from the current study build on this, by also identifying established eating behaviour as additional factor not otherwise reflected in the TM model, which is a facet of women’s preconceptual identity.…”
Section: Discussionsupporting
confidence: 94%
“…These include the physical environment and aspects of the social environment, and the influence of pregnancy symptoms. This is consistent with what has previously been reported in the literature [ 31 ]. However, the findings from the current study build on this, by also identifying established eating behaviour as additional factor not otherwise reflected in the TM model, which is a facet of women’s preconceptual identity.…”
Section: Discussionsupporting
confidence: 94%
“…This is important as neither the COM‐B nor TM model consider that the salience of their respective constructs might change at different points in time. Consequently, previous research has suggested that these models may be limited when applied to the context of pregnancy, due to the changeable nature of the pregnancy experience and the static understanding of behaviour change that these models offer (Rockliffe, Peters, Heazell, & Smith, 2021a, 2021b). It will therefore be important to further explore nuances in the salience of the constructs over time, in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the variance unaccounted for by the COM‐B constructs may therefore still reflect capability, opportunity, and motivation, but require a more sensitive measure to effectively record these aspects. With regard to the TM model, previous research has suggested that when applied to pregnancy, the model fails to account for non‐psychological factors, such as practical and environmental factors, social influences, and physical pregnancy symptoms (Rockliffe, Peters, Heazell, & Smith, 2021b). These may therefore reflect some of the unmeasured factors contributing to eating behaviour that the TM model failed to include.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Women who are less aware, or who held misconceptions about the consequences of their behaviours will be less likely to engage in behaviour change. 28 , 42 The women in our sample had limited knowledge about stillbirth and its associated risk factors; however, when prompted to speak about the advice received during their antenatal care, monitoring of fetal movements and the importance of sleep position was often mentioned. These findings are very similar to those obtained by Stacey et al 43 in a recently published study, where they explored migrant women's awareness of health messages to reduce stillbirth risk.…”
Section: Discussionmentioning
confidence: 99%